The role of hypoxia-associated miRNAs in acquired sensorineural hearing loss - Safabakhsh, Sina; Wijesinghe, Printha; Nunez, Morgan; Nunez, Desmond A. (Frontiers in Cellular Neuroscience, 2022)
Introduction: Sensorineural hearing loss (SNHL) is a prevalent sensory deficit presenting commonly as age-related hearing loss. Other forms of SNHL include noise induced and sudden SNHL. Recent evidence has pointed to oxidative stress as a common pathogenic pathway in most subtypes of acquired SNHL. MicroRNAs (miRNAs) are small non-coding RNA sequences that suppress target mRNA translation and affect downstream processes. Many studies have shown that miRNAs are integral biomolecules in hypoxia-adaptive responses. This study reviews the evidence for hypoxia-adaptive microRNAs (hypoxamirs) different types of acquired SNHL. Methods: Electronic bibliographic databases PubMed, Ovid MEDLINE, Ovid EMBASE, and Web of Science Core Collection were searched independently by two investigators for articles published in English from the inception of the database to the end of July 2020. Text word or medical subject heading searches of all fields, titles, abstracts, or subject headings depending on the database were undertaken with combinations of the words “microRNAs”, “hypoxia”, “hypoxamiRs”, “oxidative stress”, “ischemia” and “hearing loss”. The reference lists of studies meeting the inclusion criteria were searched to identify additional relevant studies. The inclusion criteria included relevant clinical studies with human subjects, animal, and in-vitro experiments. Risk of bias was assessed using the Cochrane risk of bias assessment tool for human studies and the Systematic Review Center for Laboratory animal Experimentation (SYRCLE) risk of bias assessment tool for animal model and in-vitro studies. Results: A total of 15 primary articles were selected for full text screening after excluding duplicates, reviews, retracted articles, and articles published in non-English languages. All 9 articles meeting the study inclusion criteria were from animal or in-vitro model studies and were assessed to be at low risk of bias. MiRNAs miR-34a and miR-29b were reported to be involved in SNHL in inner ear cell models exposed to oxidative stress. Signaling pathways Sirtuin 1/peroxisome proliferator-activated receptor gamma coactivator-1-alpha (SIRT1/PGC-1α), SIRT1/p53, and SIRT1/hypoxia-inducible factor 1-alpha (HIF-1α) were identified as underlying pathways involved in acquired SNHL. Conclusion: There is evidence that miR-34a and -29b are involved in oxidative stress models of acquired SNHL. Further studies are required to determine if these findings are clinically applicable.